Guide e-book on developing Android-based smart key: A learning media for the application of electronic circuits in higher education - Yuberti, Yuberti; Komikesari, Happy; Yusandika, Ajo Dian; Wibowo, Firmanul Catur; Diansah, Irani (Indonesian Journal of Science and Mathematics Education, 2024)
This study examines the feasibility and effectiveness of an Android-based smart key guide e-book as a learning medium for applying electronic circuits. Using the ADDIE model (Analysis, Design, Development, Implementation, and Evaluation), the research involved physics education students from three universities in Lampung Province, with evaluations conducted by material and media experts. Data were collected through questionnaires and documentation. Validation results indicate high feasibility, with scores of 81.75% from material experts and 86% from media experts, as well as positive responses from students in small-scale trials (88.69%) and large-scale trials (86%). Thus, the developed e-book is deemed suitable as a learning medium for electronic circuit applications learning. These findings have implications for enhancing students' practical understanding, supporting self-directed learning, and creating more engaging education in sensor and transducer topics electronic circuits application.